E-learning application Madrasah online learning solution in the middle of pandemic Covid-19 in Ma Negeri Insan Cendekia, Kendari - Husnul Khotimah; Husniyatus Salamah Zainiyati; Abdulloh Hamid; Abdul Basit (Technium Social Sciences Journal, 2020)
This Research is a qualitative research that aims to determine the benefits of using E-Learning Madrasas as a medium of distance Learning when the Covid 19 pandemic in MAN Insan Scholar Kendari City. The results show that Madrasah E-learning is able to accommodate the needs of teachers and students in distance learning in the Covid 19 pandemic ranging from planning to evaluation, also facilitating the process of monitoring teacher performance in teaching and learning activities. Even Though there is no learning in the classroom as usual the teacher can still deliver learning material to students through the Madrasah E-Learning application. Students can also access learning material and still have an assessment of learning outcomes and end of semester assessment. Based on the results of the study it can be concluded that Madrasah E-Learning can be a good medium for distance Learning. As for the obstacles that are still being experienced are Internet networks that have not been stable in certain areas in remote Indonesia.